A Single Retrograde Intramedullary Nail Technique for Treatment of Displaced Proximal Humeral Fractures in Children: Case Series and Review of the Literature. Issue 1 (January 2021) - Samara, Eleftheria; Tschopp, Benjamin; Kwiatkowski, Barbara; Vardar, Elif; Lutz, Nicolas; Zambelli, Pierre-Yves
Abstract : Background: Displaced proximal humeral fractures in older children with low remodeling potential need to be reduced and fixed. There are many options for stabilization, including external fixation, rigid internal fixation with screws and plates, percutaneous pinning, and flexible intramedullary nailing. The use of 2 flexible retrograde nails, originated at the University of Nancy, France, became the most popular technique in Europe. The aim of this study was to describe and assess a modified, single retrograde nail technique to treat fractures of the proximal part of the humerus. Methods: We performed a retrospective monocentric study. From June 2016 to May 2019, a modified retrograde nail technique with 1 prebent nail was used for the management of 21 consecutive children with a closed displaced proximal humeral fracture. Demographic and surgical data were collected. The surgical technique is similar to the classic elastic stable intramedullary nailing, but only 1 nail is used. The average surgical time and perioperative complications were used as criteria for the feasibility of this technique. Radiographs were obtained preoperatively; at 1, 4, and 6 weeks postoperatively; and after implant removal at an average of 4.2 months postoperatively. The clinical outcomes were assessed on the basis of the shoulder range of motion documented in the medical records and by using the French edition of the QuickDASH (shortened version of the Disabilities of the Arm, Shoulder and Hand [DASH] questionnaire) evaluation scale at the time of implant removal. Results: Nineteen patients with a mean age of 12.6 years and a mean follow-up of 6 months were included in the study. The mean surgical time was 49 minutes. The single intramedullary nail technique provided a satisfactory reduction of all fractures. No perioperative complication occurred. In 1 case, partial loss of reduction was observed on the first-week control radiograph. All patients had a healed fracture, no deficits, excellent results according to the QuickDASH score, a normal range of motion, and excellent strength of the shoulder joint at the time of implant removal (at a mean of 4.2 months). Conclusions: The current study confirms the feasibility and efficacy of the single retrograde intramedullary nail technique to treat displaced proximal humeral fractures in children. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.